Possible Use of Foresight, Understanding, and Planning by Wolves Hunting Muskoxen - Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2007)
On Ellesmere Island in 2006, arctic wolves (Canis lupus arctos) were observed making a two-pronged approach to a herd of muskoxen (Ovibos moschatus) and, on another occasion, ambushing muskoxen. Both observations seemed to provide evidence that the wolves were using foresight, understanding, and planning. Although the possible use of insight and purposiveness has been documented in captive wolves, the present report is one of the few to document the possibility that freeranging wolves use these other three mental processes. En 2006, sur l’île Ellesmere, des loups arctiques (Canis lupus arctos) ont été observés en train d’approcher sur deux fronts un troupeau de boeufs musqués (Ovibos moschatus) et une autre fois, en train de tendre une embuscade à des boeufs musqués. Ces deux observations portent à croire que les loups sont en mesure de prévoir, de comprendre et de planifier. Bien que le recours possible à la prévoyance et à l’intentionnalité ait été officiellement remarqué chez les loups en captivité, le présent rapport est l’un des rares documents énonçant la possibilité que les loups en liberté aient recours à ces processus mentaux.